Complex ownership and capital structure - Teodora Paligorova; Zhaoxia Xu (Bank of Canada, 2009)
This paper investigates the impact of pyramid ownership structure and multiple controlling shareholders on firm leverage. Pyramids, having at least one controlling shareholder and a subsidiary, rely significantly more on debt financing than non-pyramid firms. Moreover, higher leverage is observed in pyramids where the second controlling shareholders have more voting rights. We also find that the disparity between the voting rights of the first two controlling shareholders is negatively related to firm leverage. Interestingly, the influence of the second controlling shareholder is only present in non-family controlled pyramids. Overall, the results are consistent with the view that controlling shareholders in pyramids use debt to secure their private benefits.
Keywords: G31; G32; 330; Financial markets; International topics; Unternehmensfinanzierung; Corporate Governance; Eigentümerstruktur; Familienunternehmen; Fremdkapital; G-7-Staaten